If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 2f + f = 44 Combine like terms: 2f + f = 3f 8 + 3f = 44 Solving 8 + 3f = 44 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 3f = 44 + -8 Combine like terms: 8 + -8 = 0 0 + 3f = 44 + -8 3f = 44 + -8 Combine like terms: 44 + -8 = 36 3f = 36 Divide each side by '3'. f = 12 Simplifying f = 12
| 9+3=711 | | 2/-7x+8 | | y+11=4/5(x+12) | | 4y-1=15 | | A=2*pi*r*h | | x^22-1=0 | | 6(j+3)-23=49 | | 4x^2-56x+112=0 | | -1=-5(t-78)+69 | | 2n-3=16 | | -6(d-97)=-12 | | 268-4x=41x+18 | | 3x^2(x^2-8)+6x+5=4x^4-6x(4x-1)+4 | | 97=5(c-79)-2 | | 5-7x=38-28x | | 3(10-2)=(3*10)-(3*2) | | -7x+8/2 | | 9x-7x=18 | | 7x+x-4x-7=5x | | 5(k-78)+-96=-51 | | 9x-7x=-30 | | 3.6-x=9 | | -7(q+56)=14 | | 3erty+4erty=5ertyz | | y=6+m(x+5) | | -4=-29u | | -3x+12/2 | | 2/-3x+12 | | 9/5*-30+32 | | j-69/2=9 | | 1+3=x-18 | | 1/2*((5x+6)+(3x))*(4x-3) |